Pendampingan Pengembangan Kentang di Dataran Medium Desa Santong-Kabupaten Lombok Utara - M. Sarjan; Aluh Nikmatullah; Mery Windarningsih; Agus Purbatin Hadi (Pascasarjana Universitas Mataram, 2021)
The development of potato crops in West Nusa Tenggara Province has been carried out in the Sembalun plateau. However, the Sembalun region faces limited infrastructure support capacity, so one of the strategies to increase potato production is to expand potato development to areas outside the Sembalun region, namely to potential medium plain areas. North Lombok regency has a potential medium plain for the development of potato crops, namely in the santong area of Kayangan subdistrict and Senaru area of Bayan Subdistrict. The National Strategic Excellence Research Team of Mataram University has conducted research for the development of quality potato seeds in the Santong region, followed by the assistance of its development. The results of this sideways show from the aspect of potato cultivation can grow and produce well, but the obstacle faced is the high intensity of attacks of plant destruction organisms. The expansion into this medium plain demands technological innovation of potato production in the medium plain. Therefore, it is considered necessary to conduct sustainable assistance of potato development in North Lombok Regency